The phenomenon of the sapiential dimension of Christian mysticism in the thought of Bruno Barnhart: Sapiential understanding of reality. Justification of philosophical reflection on mysticism in general - Januszewski, Zbigniew (Filozofia Chrześcijańska, 2023)
The primary objective of this article is to give an overview and to philosophically explore the main ideas of an emerging, relatively new mystical dimension within Christianity which is called the sapiential Christianity. This paper is based mainly on the work of Bruno Barnhart (1931-2015), Camaldoli monk, mystic and theologian who spent most of his monastic life developing and systematising ideas of sapiential Christianity. This specific approach to the whole Christian tradition focuses on the Unitive Reality and its expression in the world, especially in the incarnational Christ-event, aiming towards divinisation of the whole reality. It also places a great emphasis on the position and role of human being in this process of divinisation. In the article, the philosophical analysis concentrates on the three aspects of this mystical movement: (1) epistemology, where wisdom as the way of knowing has its unique place in the whole process of gaining knowledge about Unitive Reality; (2) anthropology, where we look at the source of dignity of human person in the sapiential perspective: (3) metaphysics, where we explore the notion of the Unitive Reality and its characteristics. Overall, the purpose of this article is to show the significance and relevance of sapiential Christianity in our modern world; to encourage philosophers that are interested in religion and mysticism to explore and enter into a dialogue with this unique way of seeing the Christian tradition.